Biological soil crusts : structure, function, and management - Belnap, Jayne, 1952-; Lange, O. L. (Otto Ludwig) (New York : Springer, 2001)
In arid lands, where vegetation is sparse or absent, the open ground is not bare but generally covered by a community of small, highly specialized organisms. Cyanobacteria, algae, microfungi, lichens, and bryophytes aggregate soil particles to form a coherent skin - the biological soil crust. It stabilizes and protects the soil surface from erosion by wind and water, influences water runoff and infiltration, and contributes nitrogen and carbon to desert soils. Soil surface disturbance, such as heavy livestock grazing, human trampling or off-road vehicles, breaks up the fragile soil crust, thus compromising its stability, structure, and productivity. This book is the first synthesis of the biology of soil crusts and their importance as an ecosystem component. Composition and functioning of different soil-crust types are discussed, and case studies are used to show the impact of crusts on landscape hydrology, soil stability, nutrient cycles, and land management.
Part I: Taxonomic Composition, Ecology and Biogeography of Soil-Crust Communities * Part II: Heterotrophic Components of Biological Soil Crusts * Part III: Structure of Biological Soil Crusts: Microscale to Landscape * Part IV: Biological Soil Crusts as an Ecosystem Component: Carbon and Nitrogen Acquisition and Interactions with Vascular Plants * Part V: Soil Stability and Hydrology as Influenced by Soil Crusts * Part VI: Disturbance to Biological Soil Crusts: Resistance, Resilience and Restoration * Part VII: Monitoring and Management of Biological Soil Crusts * Part VIII: Conclusions.
Includes bibliographical references and indexes.
Keywords: Soil biology; Soil crusting; Soil ecology